Numerical investigation of an unsteady nanofluid flow with magnetic and suction effects to the moving upper plate. (February 2020) - Shuaib, Muhammad; Ali, Abbas; Khan, Muhammad Altaf; Ali, Aatif
The recent work provides the numerical investigation of an unsteady viscous nanofluid flow between two porous plates under the effect of variable magnetic field and suction/injection. Navier Stokes equations are modeled to study the hydrothermal properties of four different nanoparticles copper( Cu ), silver( Ag ), aluminum oxide( A l 2 O 3 ), and titanium oxide( Ti O 2 ) . The resultant nonlinear partial differential equations, governing the viscous fluid flow, are solved numerically using Crank–Nicolson scheme. The effect of important physical parameters such as volume fraction, magnetic strength, and porosity parameter are shown both graphically and in tabular form. It is found that due to the greatest thermal diffusivity for nanofluidAg, comparatively the velocity increases more rapidly with the increasing value of volume fraction. Due to this effect, it is preferred to use nanofluidAg for transportation purposes.